1991
DOI: 10.1063/1.350141
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and heavy fermion-like behavior in the RBiPt series

Abstract: Members of the RBiPt (R =Ce-Lu with the exceptions of Pm and Eu) series have been grown as single crystals. Magnetic susceptibility and electrical resistance have been measured on all members of the series, and specific heat measurements have been performed on rcprcscntatives. Tue high temperature resistance uniformly changes from that of a small-gap semiconductor or semimetal seen in NdBiPt to that of a heavy-fermion meta! seen in YbBiPt, which shows a linear coefficient of specific heat at low temperatures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
160
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 4 publications
20
160
1
Order By: Relevance
“…l(a) is intrinsic to YbBiPt. The resistive anomaly seen in YbBiPt at 0.45 K is qualitatively similar to those seen in other members of the RBiPt series [2]. Figure 3 There currently seem to be three possible origins of the resistive anomaly that accompanies the transition to the antiferromagnetic groundstate: (i) localized moments order and a superzone gap emerges as a result of the magnetically imposed periodicity, (ii) a spin density wave (SDW) forms out of the conduction band, also leading to a partial gapping of the Fermi surface, or (iii) there is a cooperative Jahn-Teller effect accompanying the magnetic order of localized moments that leads to a distortion of the lattice to tetragonal or lower symmetry.…”
Section: Experimental Results and Analysissupporting
confidence: 65%
See 2 more Smart Citations
“…l(a) is intrinsic to YbBiPt. The resistive anomaly seen in YbBiPt at 0.45 K is qualitatively similar to those seen in other members of the RBiPt series [2]. Figure 3 There currently seem to be three possible origins of the resistive anomaly that accompanies the transition to the antiferromagnetic groundstate: (i) localized moments order and a superzone gap emerges as a result of the magnetically imposed periodicity, (ii) a spin density wave (SDW) forms out of the conduction band, also leading to a partial gapping of the Fermi surface, or (iii) there is a cooperative Jahn-Teller effect accompanying the magnetic order of localized moments that leads to a distortion of the lattice to tetragonal or lower symmetry.…”
Section: Experimental Results and Analysissupporting
confidence: 65%
“…origin [3,7,9] and has a magnetic susceptibility consistent with antiferromagnetism [1,2,6]. In addition, the size of the ordered moment detected by ~SR measurements is 0.1p.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…1,5 A sample approximately 1.5 mm thick with smooth surfaces was chosen for the measurements, and excess flux was carefully removed from the surfaces prior to the experiments. High-energy x-ray diffraction measurements were made at station 6-ID-D at the Advanced Photon Source using an x-ray wavelength of λ = 0.09407Å and a beam size of 60 × 60 µm.…”
Section: Methodsmentioning
confidence: 99%
“…YbBiPt is a heavy-fermion compound which manifests an extraordinary Sommerfeld coefficient of ≈ 8 J/mol-K 2 and spin-density-wave type antiferromagnetic (AFM) order below a Néel temperature of T N = 0.4 K. [1][2][3][4][5][6] The low value of T N reflects the fact that the dominant magnetic energy scales are all small and comparable -the Kondo temperature T K ≈ 1 K, 2 the Weiss temperature θ W ≈ −2 K, 5 and the crystallineelectric-field (CEF) splitting is on the order of 1 -10 K. 7 As a consequence, the compound's electronic states are very responsive to small applied magnetic fields and pressures, 5,8 and recent neutron diffraction measurements have shown that the AFM order is quite fragile. 6 The magnetic phase diagram indicates that, as T → 0 K, AFM order persists up to a critical applied magnetic field of µ 0 H c ≈ 0.4 T, followed by a region of non-Fermi liquid behavior up to ≈ 0.8 T, above which Fermi-liquid behavior occurs up to at least 6 T. 5 It has been proposed that a magnetic-field-induced quantum-critical point occurs at µ 0 H c .…”
Section: Introductionmentioning
confidence: 99%